2007
DOI: 10.1016/j.juro.2006.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Trial of Spaced Education to Urology Residents in the United States and Canada

Abstract: Online spaced education improves the acquisition and retention of clinical knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 12 publications
1
65
0
Order By: Relevance
“…34 Multiple studies have demonstrated improved learning efficiency and knowledge retention using spaced education in surgical residencies and undergraduate medical education when material was delivered over months to years. 22,23,[25][26][27]35,36 Our study showed the utility of spaced education over a month-long rotation. Considerable attrition may have played a role in our inability to detect a significant difference in test performance at the 3-month follow up.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…34 Multiple studies have demonstrated improved learning efficiency and knowledge retention using spaced education in surgical residencies and undergraduate medical education when material was delivered over months to years. 22,23,[25][26][27]35,36 Our study showed the utility of spaced education over a month-long rotation. Considerable attrition may have played a role in our inability to detect a significant difference in test performance at the 3-month follow up.…”
Section: Discussionmentioning
confidence: 57%
“…Studies of surgical residents and medical students have demonstrated that spaced education initiatives spanning months to years improve learning efficiency and longterm knowledge retention. [22][23][24][25][26][27][28] Web-based spaced education may be an effective approach for residents on an emergency medicine rotation with asynchronous clinical schedules. …”
mentioning
confidence: 99%
“…6,7 We recently completed a randomized trial of spaced education using daily noninteractive (static) e-mails to 537 urology residents in the United States and Canada. 11 In this trial, residents received in-service examination study questions (1) in a bolus format 6 months before their in-service examination or (2) in a spaced-education format consisting of daily e-mails of 1-2 study questions over these 6 months. On a validated test administered at staggered time points to both groups, the spaced-education cohort demonstrated significantly greater knowledge acquisition and retention than those in the bolus cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Many participants suggested incorporating review time before the one month assessment because they could not recall the mnemonics at the test. Spaced learning has been shown to enhance retention of information or manual skill dexterity [4]. We hypothesize that both groups would fare well with spaced learning; however, we believe use of a mnemonic system would enhance efficiency of knowledge acquisition (i.e., require dramatically less study time).…”
Section: Discussionmentioning
confidence: 88%